Class, Income, and Class Consciousness of Labor Fishers - Kinseng, Rilus A.; Sjaf, Sofyan; Sihaloho, Martua (Journal of Rural Indonesia [JORI], 2015)
There have been debates on the role of class in â€œinfluencingâ€ income inequality in contemporary societies.Â Some argue that class position is no longer relevant in determing oneâ€™s income, while others argue that class still counts.Â Therefore, it is very interesting to investigate relations between class structure and income among fishers in Indonesia. Furthermore, Marxian argued that class position will determine class consciousness. Therefore, it is interesting to study the class consciousness of labor fishers in Indonesia. Analyzing relations between class structure and income as well as class consciousness of labor fishers in Indonesia is especially very interesting and important since fishers have a very typical patront-client relationships. Moreover, study of this subject in Indonesia is still limited. This study has three main objectives: first to investigate the class structure of fishers and how this structure has been formed, second to analyse the income of fishers in different class locations, and third to analyze class consciousness of labor fishers. This study uses combination of qualitative and quantitative methods. The study was conducted in Indramayu, West Java in 2013. Our analysis shows that the class structure of fishers consists of four main classes, namely large-scale, medium-scale, small-scale, and labor classes. These classes have been formed through complex and long processes, including the so-called â€œmodernizationâ€ programmes promoted by the government.Â In term of income, the study shows that there are significant differences of income among fishers in different class locations. The Gini Ratio is very high, that is 0.88. Thus, class structure does influence fishersâ€™ income significantly. Furthermore, this study finds that class consciousness of labor fishers has not fully developed yet. Labor class is a class in itself, but not class for itself. Â© 2014 Journal of Rural Indonesia [JoRI] IPB. All rights reserved.Keywords: fishers, class structure, income, class consciousness